The regulatory effect of CoL10A1 to the intracranial vascular invasion and cell proliferation in breast cancer via EMT pathway - Xiaoyin Wang; Shunchang Ma; Shaomin Li; Wang Jia; Dainan Zhang (Scientific Reports)
Abstract With advances in breast cancer (BC) treatment technology, although it could prolong the BC patients’ survival, brain metastasis (BM) is increasing gradually. Patients with brain metastasis of breast cancer (BMBC) could have the decline of survival rate and quality of life. Investigate the regulatory role of Collagen Type X Alpha 1 Chain (CoL10A1) in BMBC process was the aim of this study. CoL10A1 expression was analyzed from TCGA database and clinical tissues, and then detected the regulation of CoL10A1 on BC cells proliferation, migration, and invasion in BC cell lines and mouse models. Our findings indicated that BMBC tissues have significant levels of CoL10A1 expression. BC cells proliferation, migration and invasion may be inhibited by knocking down Co10A1 in vitro and in vivo. In addition, we found that knocking down CoL10A1 could reduce the penetration of 468 cells into hCMEC/D3 cells. Knocking down CoL10A1 regulated the epithelial-mesenchymal transition (EMT) pathway related proteins expression. CoL10A1 could regulate BC cells proliferation, migration and invasion, affect the penetration into hCMEC/D3 cells in vitro, and inhibit the intracranial vascular invasion in mouse models. These results suggested that CoL10A1 may be a new target for treating human BMBC.